Comparative metal distribution in scalp hair of Pakistani and Irish referents and diabetes mellitus patients - Afridi, Hassan Imran; Kazi, Tasneem Gul; Brabazon, Dermot; Naher, Sumsun; Talpur, Farah Naz (Clinica chimica acta, 2013)
The essential metals, chromium (Cr), magnesium (Mg), manganese (Mn) and zinc (Zn), are necessary for many metabolic processes and their homeostasis is crucial for life. The toxic metals, cadmium (Cd) and lead (Pb), have no beneficial role in human metabolism. The aim of this study was to investigate the levels of Cd, Cr, Mg, Mn, Pb, and Zn in scalp hair samples of type 2 diabetes mellitus patients of both genders, ages ranging from 30 to 50y, and belong to urban areas of Ireland and Pakistan. For comparison purposes, age matched non-diabetic subjects of both countries were selected as referents. The concentrations of metals in scalp hair samples were measured by inductively coupled plasma atomic emission spectrophotometer and atomic absorption spectrophotometer after microwave-assisted acid digestion. The validity and accuracy of the methodology were checked by conventional wet-acid-digestion method and using certified reference materials. The mean values of Cd and Pb were significantly higher in scalp hair samples of both Pakistani and Irish diabetic patients as compared to referents of both countries (P<0.001). In contrast, lower Cr, Mg, Mn, and Zn (P<0.01) concentrations were detected in scalp hair derived from patients with type 2 diabetes versus healthy subjects of both countries. This study showed that, increased toxic elements and decreased essential elements are associated with diabetes mellitus. Therefore, these elements may play a role in the development and pathogenesis of diabetes mellitus. ► Scalp hair samples of Pakistani and Irish referents and DM patients were analysed for trace elements. ► The deficiency of essential trace and high levels of toxic metals was observed in DM. ► The essential elements may play a role in the development and pathogenesis of DM.